Iwona Piechnik & Marta Wicherek (eds.), Langues romanes non standard - Komorowska, Agata (Studia Romanica Posnaniensia, 2023)
Reseñas: Iwona Piechnik & Marta Wicherek (eds.), Langues romanes non standard (Agata Komorowska).